Design of an active seed throwing and cleaning unit for pneumatic rice seed metering device - Xing, He; Wang, Zaiman; Luo, Xiwen; Zang, Ying; Yang, Wenwu; Zhang, Minghua; Ma, Yuexin (International Journal of Agricultural and Biological Engineering, 2018)
To address the clogging of the rice seed metering device after a long period of operation without affecting the precision of normal seeding, an active seed throwing and cleaning unit was designed based on the fact that magnets of the same pole were mutually exclusive. The working principle of the two devices was analysed theoretically, and a mechanical model was created according to the relationship between the repulsion forces of magnets and the spring forces of springs. The super hybrid rice Y-2 You 900 with 22.5% moisture content (wet basis) was used as the test object. The whole factor experiments were carried out under different negative pressures, rotational speeds of the suction plates, and lengths of probes. The results indicated that under any test conditions, the active seed throwing and cleaning unit worked normally. The results of high-speed photography showed that the rate of seed cleaning was 100%. The results also showed that the optimal negative pressure was 0.8 kPa. The probability of 1-3 seeds per hill for the seed metering device was approximately 95% under the optimal negative pressure. The optimal length of the probe was found to be 2 mm. The average qualified rate of hill space was 96.04% under the optimal length of probe, the longer the length of the probe, the lower the qualified rate of hill space. It also showed that an active seed throwing and cleaning unit could effectively avoid the hole clogging caused by the long-term operation and had no influence on the normal operation of the pneumatic rice seed metering device. The active seed throwing and cleaning unit improved the stability of the seed metering device, and the research provided a reference for the optimal design of seed throwing and cleaning structures of the pneumatic rice seed metering device.Keywords: agricultural machinery, seed metering device, seed cleaning, anti-clogging, pneumatic seed metering, precision seederDOI: 10.25165/j.ijabe.20181102.3844Citation: Xing H, Wang Z M, Luo X W, Zang Y, Yang W W, Zhang M H, et al. Design of an active seed throwing and cleaning unit for pneumatic rice seed metering device. Int J Agric & Biol Eng, 2018; 11(2): 62–69.